RENEWABLE ENERGY PROSPECTS AS ONE OF SUSTAINABLE DEVELOPMENT DIRECTION IN SOME SOUTH RUSSIAN REGIONS - Natalia V. Bondarchuk; Ekaterina S. Titova (Юг России: экология, развитие, 2017)
Abstract. Aim. To undertake the analysis of renewable energy development trends as one of the direction in sustainable development strategy, also to define renewable energy production and using prospects in some South Russian regions. Results. Obvious tendency of increasing renewable energy production in different countries is represented by investment volume increasing materials. Innovative activity during last ten years has led solar, wind also bioenergy production development to the economically viable level. In particular, there was a number of biotechnology solutions provided creation enterprises producing second and third generation biofuel. For this reason, renewable energy production provides an opportunity to waste conversion and forms supposition for negative anthropogenic environmental impact decreasing. Taking into attention the existence of demographic, climatic, economical and geographic and some other characteristics the analysis of current condition and development prospects of renewable energy production in South Russia regions: the Astrakhan and Rostov Regions, Republic of Crimea (Southern Federal District), the Stavropol Territory (North Caucasian Federal District) has been conducted. Main conclusions. Presented facts show the beginning of renewable energy production development which can become possible because of state and regional programs, also private initiatives. In near-term prospect this development may cause significant economical results and improve ecological situation